Simultaneous vaccination against seasonal influenza and COVID-19 among the target population in Italy - Sansone, Vincenza; Miraglia del Giudice, Grazia; Della Polla, Giorgia; Angelillo, Italo Francesco (Frontiers in Public Health, 2024)
Introduction Annual influenza and COVID-19 vaccinations are effective tools for reducing the disease burden. The goals of the present cross-sectional survey were to investigate attitudes and behaviors toward the simultaneous vaccination against seasonal influenza and COVID-19 and the factors associated. Methods Questionnaires were self-administered or researcher-administered between October 2023 and February 2024 in an immunization center in the southern part of Italy. Results All 151 subjects eligible for influenza and COVID-19 vaccinations who attended the center agreed to participate. A total of 59.9% of respondents received concurrent seasonal influenza and COVID-19 vaccinations. Those who perceived that the simultaneous vaccination was safer and those who have been infected by SARS-CoV-2 fewer times were more likely to have simultaneously received both vaccinations. Regarding the reasons reported, half of the sample stated that the simultaneous vaccination was safe and that they were adequately informed. This was more likely indicated by the respondents who had received at least four doses of the COVID-19 vaccination. Among those who had not received the simultaneous vaccination, 70.7% and 29.3% had received only seasonal influenza and COVID-19. Conclusion Educational health communication campaigns are necessary to improve compliance with simultaneous administration of seasonal influenza and COVID-19 vaccinations and to increase the unsatisfactory coverage.